2019
DOI: 10.28991/cej-2019-03091251
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Densification Properties of Clay Soil Mixes with Tire Waste

Abstract: The annual increase in production of industrial wastes, including scrap tire, has created several challenges for societies. Incorporating the wastes as raw materials has been proposed in different industries, using waste tire as physical additives and investigating the geotechnical properties of this mixture can reduce the environmental pollution, as well as offering economic and technical benefits. Clay soils are abundant in southern regions of Tehran where scrap tire is also produced in large quantities ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The CBR values were also increased considerably where unsoaked CBR value was found to be maximum at 10.65% for 12% shredded tyre while soaked CBR value was found to be maximum at 6.84% for 12% shredded tyre. Akbarimehr et al [11] investigated the effect of waste tyre granules and powdered formed on Tehran clay soil. The waste tyres were added at 2, 4, 6, 8, 10, 20 and 30% weight and Proctor compaction tests were performed.…”
Section: Introductionmentioning
confidence: 99%
“…The CBR values were also increased considerably where unsoaked CBR value was found to be maximum at 10.65% for 12% shredded tyre while soaked CBR value was found to be maximum at 6.84% for 12% shredded tyre. Akbarimehr et al [11] investigated the effect of waste tyre granules and powdered formed on Tehran clay soil. The waste tyres were added at 2, 4, 6, 8, 10, 20 and 30% weight and Proctor compaction tests were performed.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial waste materials have been employed as additives to improve the properties of soils. In previous studies on soil improvement, some additives that were commonly used for this purpose, including recycled asphalt pavement (RAP) [10,11], cement by-pass dust, also known as cement kiln dust (CKD) [12,13], pond ash (PA) [14], steel slag (SS) [15][16][17], end-of-life tires (ELT) [18][19][20], fly ash (FA) [21,22], rice husk ash (RHA) [23,24], waste stone powder (WSP) [25,26], construction and demolition waste (CDW) [27][28][29], waste glass (WG) [30][31][32][33], and coffee wastes (CW) [34,35]. These studies have shown that using recycled or waste materials is effective in increasing the engineering properties of soil mixtures and providing a quality control method for their applications in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional soil improvement techniques, such as densification, dynamic compaction, stone columns, and chemical grouting have been successfully employed to enhance the engineering characteristics of various soils [1,2]. Nevertheless, these techniques have some setbacks due to their potential adverse environmental effects [3].…”
Section: Introductionmentioning
confidence: 99%